Sources of value creation through private equity-backed mergers and acquisitions: The case of buy-and-build strategies - Mariela Borell; Diana Heger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This article documents a new value creation function of private equity investors who carry out buy-and-build strategies. Buy-and-build strategies constitute an initial acquisition of a firm, serving as a 'platform', by a private equity investor and follow-on private equity-backed acquisitions ('add-ons'). The investor merges the platform and add-ons into a single entity. Additionally to the selection of well performing firms by the investors prior to the transaction, we identify value-enhancing potentials which private equity investors explore through buy-and-builds. The investors bring together platforms with lower capacity utilization and lower returns, and add-ons with higher utilization and higher returns in order to allocate resources and capacity more efficiently and to improve firms' performance. However, the buy-and-build strategies only have a positive impact on the profitability of firms with increasing industry adjusted utilization. Consequently the more efficient deployment of assets for the generation of sales drives the improved performance after buy-and-builds.
Keywords: G24; G34; L14; 330; Private Equity; Buy-and-Build